Spontaneous transvaginal bowel evisceration - Chhabra, Sarabjeet (Medknow Publications & Media Pvt Ltd, 2013)
Transvaginal prolapse of bowel segments after major abdominal surgery is of rare occurrence and is commonly reported to follow after hysterectomy and enterocele repair. However, spontaneous bowel evisceration through vagina following cystectomy is even rare. We report and discuss a case of spontaneous transvaginal bowel evisceration in a postmenopausal woman with the intent of increasing its awareness among surgeons and proposing a precautionary measure for this entity.